A critical discourse analysis of news discourse on in The Times. - Guo, Rubing (Human Resource Management Academic Research Society (HRMARS), 2023)
The Brexit event has attracted wide attention from the world since its occurrence and has a significant impact on the world development pattern and the global economy. For ordinary people, news is not first-hand information, but the product of processing by news agencies and journalists, so news discourse is an effective way to spread ideology-news discourse is an effective way to spread their ideologies who wrote this discourse by using various language strategies. This study examines and reveals how news reporting is ideological. It looks at how The Times uses language to spread ideologies. Based on the analytical model of Fairclough from the perspective of critical discourse analysis, this study analyzed 50 news reports concerning the issue of Brexit from The Times ( from 23 June 2016 to 31 Dec. 2020). Both quantitative analysis and qualitative analysis are employed to explore the linguistic features. The findings highlight how the Times represents Brexit in its reporting and how the representations favor the interests of the party or particular groups. The findings of the study are as follows: Firstly, language is not used randomly when it comes to news reporting. Secondly, the different camps portrayed different images of the EU and the UK government. The findings show how news language is laden with ideological meanings and orientations and only a critical investigation can reveal that the news media use various discursive strategies when reporting important issues and that these strategies are ideological biased.